EFISIENSI DAN DOSIS OPTIMUM PUPUK P DAN HASIL JAGUNG PULUT (Zea mays ceratina L.)YANG DIINOKULASI DENGAN BAKTERI PELARUT FOSFAT (BPF) INDIGEN DI ALFISOL - Jansen, Gregorius Putra; Benggu, Yoke Ivonny; Kapa, Max Junus; Airtur, Moresi; Ishaq, Lily F. (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Nusa Cendana, 2024)
The use of phosphate-solubilizing microorganisms combined with chemical fertilizers is very important, especially in soils that contain a lot of calcium. This is due to orthophosphate ions easily bind to calcium and these microorganisms are able to dissolve the fixed phosphate. The research has been conducted at the Faperta Undana experimental garden and took place from June 2023 to February 2024. The purpose of this study was to determine the interaction between phosphate-solubilizing bacteria (PSB) inoculation and phospahate fertilizer on the availability of P, population of PSB, fertilization efficiency and yield of glutinous corn, and to identify the combination that give the best result on the variables observed. The study was designed using a Completely Randomized Design. The first factor was PSB inoculation that consists of : without PSB inoculation and indigenous PSB inoculation. The second factor was the dose of P fertilizer with five levels as follows: 0%, 25%, 50%, 75%, and 100%. Data were analyzed using analysis of variance, followed by the Duncan Multiple Range Test if significant effects were found. Observed variables included PSB population, available P, fertilization efficiency, weight of corn without husks. The results showed that the interaction between PSB inoculation and the dose of SP-36 fertilizer had a significant effect only on fertilization efficiency. The single factor of PSB inoculation significantly affected the availability of P and PSB population, while the single factor of SP-36 fertilizer dose significantly affected fertilization efficiency, available P, and corn weight per cob without husks.